What can space radiation protection learn from radiation oncology?. (August 2021) - Tinganelli, Walter; Luoni, Francesca; Durante, Marco
Abstract: Protection from cosmic radiation of crews of long-term space missions is now becoming an urgent requirement to allow a safe colonization of the moon and Mars. Epidemiology provides little help to quantify the risk, because the astronaut group is small and as yet mostly involved in low-Earth orbit mission, whilst the usual cohorts used for radiation protection on Earth (e.g. atomic bomb survivors) were exposed to a radiation quality substantially different from the energetic charged particle field found in space. However, there are over 260, 000 patients treated with accelerated protons or heavier ions for different types of cancer, and this cohort may be useful for quantifying the effects of space-like radiation in humans. Space radiation protection and particle therapy research also share the same tools and devices, such as accelerators and detectors, as well as several research topics, from nuclear fragmentation cross sections to the radiobiology of densely ionizing radiation. The transfer of the information from the cancer radiotherapy field to space is manifestly complicated, yet the two field should strengthen their relationship and exchange methods and data.